Autopsy Study to Analyze Correlation between Survival Period & New Injury Severity Score of Thoraco Abdominal Injuries in Fatal Road Traffic Accident Cases - Pratima R. Bhat; Pratibha R. Kulkarni (Indian Journal of Forensic Medicine and Pathology, 2026)
Introduction: Leading causes for mortality and morbidity among young, productive group of population is thoraco abdominal trauma brought on by traffic accidents. Most basic use of injury severity grading is probably in predicting period of survival following trauma. Aim: Study’s aim is to analyze correlation between survival period & new injury severity score. Materials and methods: 105 Road traffic accident autopsy cases involving thoracoabdominal injuries brought to morgue of Belagavi Civil Hospital and Dr. Prabhakar Kore Hospital were taken for study. Universal sampling method was used for calculating sample size. Results: The new injury severity score (NISS) was 51-75 in total 65 (61.9%) cases. When age group of 21-40 years was evaluated NISS was 51-75 in about 34 cases. When the period of survival was less than 2 hrs NISS was 51-75 in 28 cases, when period of survival was 2-6 hours NISS was 51-75 in 20 cases. However when period of survival was more than 1 week NISS score was 0-25. Conclusion: Injury severity score had very high negative correlation with period of survival that means victims who had very high injury ISS had very less survival period. Highlights: Trauma scores help in determining quality of treatment and thereby reducing mortality. Study’s aim is to analyze correlation between survival period & new injury severity score. Study’s conclusions and outcomes will help shape policies and actions to reduce death rates and morbidity rates from injuries to the abdomen and thorax.